1990
DOI: 10.1111/j.1439-0450.1990.tb01123.x
|View full text |Cite
|
Sign up to set email alerts
|

A Basic Study of Chemotaxis of Leptospiras

Abstract: Summary Chemotaxis of leptospiras was studied using a U‐tube made of a commercially available straw‐shaped polypropylene tube with an uneven flexible part. The U‐tube was made by folding the polypropylene tube double and binding the vertical parts by a piece of tape, thus making the uneven flexible part the bottom. Semi‐solid Korthof's medium was poured into the U‐tube. Preliminary experiments showed that the medium containing 0.5 % agar and measuring 2 cm in length was appropriate. Leptospiras inoculated on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Genome sequence analyses of Borrelia burgdorferi, Treponema pallidum, and Treponema denticola revealed that these spirochetes not only have complete flagellum-based motility systems but also possess the genes necessary for chemotaxis that could direct the flagellar movement (6, 7, 11, 14, 22a, 54; see also data available at www.tigr.org). Earlier experiments in our laboratory as well as those of other groups have also indicated that pathogenic spirochetes do indeed perform chemotaxis towards substances present at their site of infection (15,19,23,30,33,52,63). Based on these findings, we have hypothesized that chemotaxis may play a role in guiding motility of pathogenic spirochetes during penetration and further invasion of the host tissues (28).…”
mentioning
confidence: 73%
“…Genome sequence analyses of Borrelia burgdorferi, Treponema pallidum, and Treponema denticola revealed that these spirochetes not only have complete flagellum-based motility systems but also possess the genes necessary for chemotaxis that could direct the flagellar movement (6, 7, 11, 14, 22a, 54; see also data available at www.tigr.org). Earlier experiments in our laboratory as well as those of other groups have also indicated that pathogenic spirochetes do indeed perform chemotaxis towards substances present at their site of infection (15,19,23,30,33,52,63). Based on these findings, we have hypothesized that chemotaxis may play a role in guiding motility of pathogenic spirochetes during penetration and further invasion of the host tissues (28).…”
mentioning
confidence: 73%
“…Borrelia burgdorferi recognizes serum as an attractant and H 2 O 2 , nonphysiological pH (Ͼ8.5 or Ͻ6.8), KCl, CaCl 2 , and small alcohols as repellents (47). Brachyspira hyodysenteriae responds to mucin, fucose, galactose, lactose, serine, cysteine, and blood (29,39), while Leptospira interrogans responds to hemoglobin (25,51). Spirochaeta aurantia performs chemotaxis towards glucose, xylose, and various other carbohydrates (21), whereas for Treponema denticola glucose, rabbit serum, albumin, and growth medium are all attractants (32,48).…”
mentioning
confidence: 99%
“…It is not known whether leptospires approach skin randomly or by a specific route. An investigation in our laboratory with a virulent strain of Leptospira interrogans serovar copenhageni and semisolid Korthof's medium in a U-shaped polypropylene tube showed chemotaxis of leptospires toward hemoglobin (4). Takamoto, of our laboratory (5a), found that no chemotaxis of leptospires toward hemoglobin occurred when the strain was not sufficiently virulent.…”
mentioning
confidence: 85%